Pola Komunikasi Kyai dan Solidaritas Jamaah - Arif Nurjaman (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
The purpose of this study was to determine the pattern of clerics communication with the Jamaat, communication patterns is more geared to the form and communication systems clerics in solidarity pilgrims and consistency of communications made clerics. This research was conducted by using the theory of communications, identity and solidarity theory. Using the paradigm of constructivism and sosilogis approach. The method used in this study is the case study method. Based on the analysis of the data in the field can be concluded that the communication patterns in solidarity Jamaat religious scholars are: (1) communication patterns of action, (2) communication patterns of interaction, and (3) communication patterns of transactions. Identity clerics influenced through personal communication layer, layer enactment, relational and communal, all forming a communication identity.